Preliminary observations on the milk production of Boran type cattle in Ethiopia - Glen, J.C.; Tessema, S.; Mziray, P; Holland, L. (1963)
The milk production of five zebu cattle from south-western Ethiopia was estimated. Calves were weighed before and after suckling three times a day, seven days each week. Average daily production for a 14-week period was 11.14, 9.39, 8.11 and 7.37 lb. of milk. Daily gains for calves of these cows in the same order as above were 1.32, 1.26, 1.02, 1.04 and 0.93 lb. No peak of production was noted during the course of the experiment nor was there any marked decrease in production up to the end of the experiment.